Faktor-faktor yang Mempengaruhi Kelengkapan Dokumentasi Asuhan Keperawatan dalam Rekam Medis Elektronik - Mardianti, Alis; Budiman, Budiman; Oyoh, Oyoh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study is to identify the factors that influence the completeness of nursing care documentation in electronic medical records in the inpatient ward of Sumber Waras Hospital Cirebon. This research was conducted in the inpatient ward of Sumber Waras Hospital Cirebon. The research method used is descriptive correlational with a cross-sectional approach. The sample size for this study was 107 nurses using purposive sampling technique. Data collection was conducted using questionnaires and checklists. Univariate analysis was presented in frequency distribution tables, bivariate analysis using chi-square test, and multivariate analysis using logistic regression. The results of the study showed that most respondents had good knowledge (54.2%), strong motivation (96.3%), light workload (50.5%), effective electronic medical record format design (51.4%), and adequate head nurse supervision (61.7%). The analysis of the relationship between knowledge, motivation, workload, and head nurse supervision with the completeness of nursing care documentation showed p-values of 0.788 (knowledge), 0.248 (motivation), 0.407 (workload), and 0.322 (supervision), indicating no significant relationship. In contrast, the relationship between the design of the electronic medical record format and the completeness of nursing care documentation showed a p-value of 0.008 (<0.05), indicating a significant relationship. In conclusion, the analysis of the relationship between knowledge, motivation, workload, and head nurse supervision with the completeness of nursing care documentation showed no significant relationship. On the other hand, the design of the electronic medical record format proved to have a significant relationship with the completeness of nursing care documentation. Keywords: Knowledge, Motivation, Workload, Supervision, Electronic Medical Records, Nursing Care Documentation